A Case of X-Linked Hypophosphatemia: Exploring the Burden in a Single Family and the Significance of a Multidisciplinary Approach - Kaler, Amrit Kaur; Bora, Nandini Shyamali; P, Kavyashree; Nikam, Ankita; Rane, Samrudhi; Tiwarekar, Yash; Limaye, Shweta; Juneja, Archana (Archives of Case Reports, 2023)
A 46-year-old lady was diagnosed clinically with X-linked hypophosphatemia (XLH) with a rare pathogenic variant detected using exome sequencing. Phosphate-regulating endopeptidase homologous X linked (PHEX) is normally expressed in osteoblasts and osteocytes, and senses phosphate regulation. More than 1000 PHEX variants have been detected to date, which are caused by missense, nonsense, and frameshift mutations in addition to splice variants and copy number changes. The aberration in the PHEX gene leads to the upregulation of fibroblastic growth factor 23 (FGF23), which leads to defects in phosphate metabolism. This results in impaired bone growth and mineralization, short and disproportionate stature, leg bowing, musculoskeletal pain, spontaneous dental abscesses, rickets, and osteomalacia in XLH patients. The spectrum of manifestations differs between pediatric and adult patients. In our case study, two of the patient’s children started showing symptoms at a younger age, unlike their mother. Timely diagnosis and the start of treatment would help in their better management and improved quality of life.